Dermatologists Communication Skills and Performance From Point of View of Patients - Farajtabar Nashli, Nasim; Hatami, Parvaneh; Aryanian, Zeinab; Rahimi Foroushani, Abbas; Robati, Reza; Goodarzi, Azadeh; Assadi, Masoud; Ghandi, Narges (Dermatology Practical & Conceptual, 2023)
Introduction: Effective communication is an important issue in patient-doctor interaction which is even more important regarding chronic disorders which need a strong relationship between patient and clinician for better compliance and optimal control disease. Objectives: This study was aimed to develop the best cultural adapted Persian version of the 28-item Calgary- Cambridge Observation Guide (CCOG) questionnaire. Methods: In this descriptive‑analytic study, data collected from 400 patients attending the outpatient dermatology clinics of 3 major hospitals in Tehran using the modified Persian version of CCOG questionnaire, both before and after being visited by dermatologists. Results: The difference of CCG scores for all of questions, except for questions number 1,16 and 22, was statistically significant. The highest score, both before and after visiting, attained by question regarding being respectful. The lowest scores for necessary behavior and the adequate amount of execution were related to questions number 3 (Introducing self) and 4 (Introducing role), respectively. Age and educational level of patients were significantly correlated with their expectations regarding communication skills of clinician. Conclusions: This study showed the acceptable validity of modified Persian version of CCOG-24 item questionnaire. Our findings also demonstrated that there was a significant difference between what patients expected from a dermatologist and the manner they actually were treated regarding physician communication skills.